DEVELOPMENT OF MARKERLESS BASED AUGMENTED REALITY INTERACTIVE LEARNING MEDIA OF 3D GEOMETRY SHAPES - Krisna Pranajaya, I Gede Ananda; Pinontoan, Benny; Ketaren, Eliasta (STMIK TIME, 2024)
Education is one sector that continues to experience significant development, especially in terms of the use of information and communication technology (ICT) in the learning process. This research is intended as a development in terms of creating an Augmented Reality 3D geometry shapes interactive learning based on the previous researches featuring a Markerless Based, that is expected to be more effective to use. The conclusion of this research is that Markerless Based Augmented Reality Interactive Learning media of 3D Geometry Shapes has been be developed succesfully. The application development stage was successfully carried out by applying the waterfall model and obtained successful results in the testing plan on the Black Box Testing of application prototypes on mobile android devices, indicates that the developed application has fulfilled all the functional requirements.